Using Literary Theory to Read Games: Power, Ideology, and Repression in Atlus’ Growlanser: Heritage of War - Quijano-Cruz, Johansen (Eludamos: Journal for Computer Game Culture, 2008)
This article argues that although many people state that literary theorists are attempting to take over the field of game studies, there has yet to be a real attempt to apply literary theory to a close reading of specific games. The article then proceeds to apply Althusser's and Foucault's ideas of power and state aparatuses to Growlanser: Heritage of War in an attempt to demonstrate that to find out the messages that games are proposing literary theory could be applied.